Genome-wide association reveals contribution of MRAS to painful temporomandibular disorder in males. Issue 3 (March 2019) - Smith, Shad B.; Parisien, Marc; Bair, Eric; Belfer, Inna; Chabot-Doré, Anne-Julie; Gris, Pavel; Khoury, Samar; Tansley, Shannon; Torosyan, Yelizaveta; Zaykin, Dmitri V.; Bernhardt, Olaf; de Oliveira Serrano, Priscila; et al.
Abstract : Abstract: Painful temporomandibular disorders (TMDs) are the leading cause of chronic orofacial pain, but its underlying molecular mechanisms remain obscure. Although many environmental factors have been associated with higher risk of developing painful TMD, family and twin studies support a heritable genetic component as well. We performed a genome-wide association study assuming an additive genetic model of TMD in a discovery cohort of 999 cases and 2031 TMD-free controls from the Orofacial Pain: Prospective Evaluation and Risk Assessment (OPPERA) study. Using logistic models adjusted for sex, age, enrollment site, and race, we identified 3 distinct loci that were significant in combined or sex-segregated analyses. A single-nucleotide polymorphism on chromosome 3 (rs13078961) was significantly associated with TMD in males only (odds ratio = 2.9, 95% confidence interval: 2.02-4.27, P = 2.2 × 10 −8 ). This association was nominally replicated in a meta-analysis of 7 independent orofacial pain cohorts including 160, 194 participants (odds ratio = 1.16, 95% confidence interval: 1.0-1.35, P = 2.3 × 10 −2 ). Functional analysis in human dorsal root ganglia and blood indicated this variant is an expression quantitative trait locus, with the minor allele associated with decreased expression of the nearby muscle RAS oncogene homolog ( MRAS ) gene (beta = −0.51, P = 2.43 × 10 −5 ). Male mice, but not female mice, with a null mutation of Mras displayed persistent mechanical allodynia in a model of inflammatory pain. Genetic and behavioral evidence support a novel mechanism by which genetically determined MRAS expression moderates the resiliency to chronic pain. This effect is male-specific and may contribute to the lower rates of painful TMD in men. Abstract : Supplemental Digital Content is Available in the Text.A polymorphic locus associated with a protective effect against painful temporomandibular disorder in males regulates the expression of the muscle RAS oncogene homolog ( MRAS ) gene.